Joseph Ratzinger's Contribution to the Preparatory Debate of the Dogmatic Constitution "Dei Verbum" - Lam, Joseph C. Quy (Gregorianum, 2013)
The dogmatic Constitution Dei Verbum is seen by many commentators as the turning point of Vatican II. Its solemn promulgation in November 18th, 1965 by Pope Paul VI brought finally to conclusion the many debates, but also the fruitful collaboration between pastors and theologians. This paper examines in particular the contribution of Joseph Ratzinger to the early debate of Dei Verbum. While many theologians have provided their critical assessments of the text de fontibus revelationis at the request of ecclesiastics, Ratzinger's role and inputs during this early discussion of the document were the outcome of his habilitation on Bonaventure's conception of revelation and, perhaps more importantly, a result of his liaison with the influential Archbishop of Cologne Cardinal Josef Frings. La Costituzione dogmatica Dei Verbum è vista da molti commentatori come il punto di svolta del Concilio Vaticano II. La sua promulgazione solenne, il 18 Novembre 1965, ad opera di Papa Paolo VI, portò a conclusione i numerosi dibattiti, ma anche la proficua collaborazione, tra pastori e teologi. Questo articolo esamina in particolare il contributo di Joseph Ratzinger al dibattito iniziale sulla Dei Verbum. Mentre molti teologi hanno fornito le loro valutazioni critiche sul testo de fontibus revelationis alla richiesta dei padri conciliari, il ruolo e i contributi di Ratzinger durante la discussione iniziale del documento, hanno avuto come risultato la sua legittimazione della concezione di Bonaventura sulla rivelazione e come conseguenza, probabilmente ancora più importante del precedente, il legame con l'influente arcivescovo di Colonia, il cardinale Josef Frings.